Assignment and modeling of the 13CH4 cold absorption spectrum in the 5471–5852 cm−1 spectral range. (September 2019) - Starikova, Evgeniya; Sung, Keeyoon; Nikitin, Andrei V.; Rey, Michael
Highlights: High resolution 13 CH4 absorption spectrum at 80 K was analyzed in the 5471–5852 cm −1 region. 3251 line positions were theoretically modeled with rms deviation of 0.0013 cm −1 . 1624 experimental line intensities were fitted with rms deviation of 9%. Assigned experimental and theoretical line lists at 80 K are provided. Abstract: This work continues our investigation on the high resolution infrared 13 C-enriched spectrum of methane recorded on a Bruker IFS-125HR Fourier transform spectrometer at 80 K in the 4970–6200 cm −1 range. In this paper we report the results of assignment and modelling of the line positions and intensities of 13 CH4 in the range between 5471 and 5852 cm −1, corresponding to the middle part of Tetradecad. The analysis was performed using a non-empirical effective Hamiltonian (EH) derived from the ab initio potential energy surface (PES) by high-order Contact Transformations (CT). The EH parameters were empirically optimized during the treatment of experimental data. In total, 3297 lines belonging to nine cold bands of the Tetradecad of 13 CH4 were assigned in the 5471–5852 cm −1 range up to J max = 11. The 3297 lines included correspond to 91% of the total line number in the region. Among them, 3251 line positions were fitted with an rms deviation of 1.33×10 −3 cm −1 . Measured line intensities for 1624 transitions were modeled using the effective dipole transition moments approach with an rms deviation of about 9%. Finally, the observed transitions were incorporated to fit simultaneously the 13 CH4 Hamiltonian parameters for the {Ground state/Dyad/Pentad/Octad/Tetradecad} system and the dipole moment parameters for the Ground state - Tetradecad system.